The development and application of a lipopolysaccharide immune challenge model using zebrafish (Danio rerio) to assess mitigation by 6-gingerol - Nicole Moran; Kristen Lamers; A. Michelle Edwards; Niel A. Karrow (Comparative Immunology Reports, 2024)
As global aquaculture expands, new methods of improving fish health are being investigated. Immunomodulators, which are capable of improving the host response to pathogens, may be useful in this respect. When assessing efficacy of immunomodulators, fish age and housing conditions should be considered. In this study, larval zebrafish (Danio rerio) from parents of different ages were immune challenged between 72 and 96 h post fertilization (hpf) with lethal concentrations of lipopolysaccharide (LPS) from Pseudomonas Aeruginosa, and mortality was assessed. Maternal age had a significant effect on survival, with offspring from 6-month-old females being most susceptible to LPS. Then, mitigation potential of 6-gingerol was assessed by pre-exposing larvae, grouped, or housed individually, from parents of different ages to various concentrations of 6-gingerol between 24 and 72 hpf. At 72 hpf, larvae were immune challenged in egg water containing no LPS (control), or LPS (52.5 or 57 μg/mL) and survival was recorded at 96 hpf. While LPS exposure resulted in mortalities, 6-gingerol did not protect individual larvae from 6-month-old parents against LPS challenge. However, group housed larvae from parents of 18 months of age demonstrated some level of protection against LPS provided by 6-gingerol. This study provides preliminary evidence that 6-gingerol may be beneficial for supporting fish health, and that age and housing conditions can act as confounders.